Tackling municipal growth dependencies through the ‘common good’. Municipal-led collaborative housing in Freiburg’s Kleineschholz development - Schmid, Benedikt (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
This paper examines the potential of centering the common good in urban development as a way to address municipal growth dependencies – the structural link between market performance and municipalities’ capacity to fulfil their responsibilities. It builds on growing evidence of the contradictions and limits inherent in marketization and financialization. Using a practice-theoretical approach, the paper develops a perspective for tracing how municipal growth dependencies are enacted and negotiated in everyday practice. In doing so, it highlights the partial agency of local authorities as they navigate between market-driven and common-good-oriented forms of development. Empirically, the paper analyses Kleineschholz, an ongoing district development project in Freiburg, Germany, that explicitly departs from short-term calculation in favour of long-term, strategic planning. Through concept-based tendering, the local authority exclusively addresses actors it deems oriented toward the common good, such as collaborative housing groups. The findings show that a strong – though imperfect – culture of communication, combined with flexible use of planning and building law instruments, enables permanent rent reductions below market rates and supports the emergence of a needs-oriented neighbourhood economy. These developments point toward more equitable provisioning systems that increase resilience from economic cycles. At the same time, persistent barriers to participation, the creation of new building stock, and the context-specific nature of Kleineschholz raise critical questions regarding overall sustainability impacts and the broader transferability of the model.
Keywords: Urban planning; common good; growth dependency; concept-based tendering; collaborative housing; Freiburg